Oil Price Fluctuations and Facilities Investment in South Africa - Rudolph, Makhathini Lungani; Aliamutu, Kansilembo (Journal of Ecohumanism, 2025)
This research explored the impact of oil price fluctuations on facilities investment in South Africa, using time series data from 2013 to 2023. The data has been studied via cointegration, variance decomposition, and impulse response analysis to ascertain the impact of fluctuations in oil prices on facilities investment in South Africa. The trend analysis indicates that oil prices and government investment on infrastructure exhibit concurrent fluctuations. The impulse response indicated that the effect of crude oil price shocks is significant in the near term yet maintains constant and increases in the long term, suggesting that the influence of crude fluctuations in oil prices may last into the future. The research results indicate that the government should pursue other financing methods for infrastructure due to the unpredictability of oil prices.